Expression Analysis of RbBP6 in human cancers: a Prospective biomarker. Issue 8 (September 2019) - Mbita, Zukile; Hull, Rodney; Mbele, Mzwandile; Makhafola, Tshepiso; Dlamini, Zodwa
Abstract : Retinoblastoma binding protein 6 (RBBP6) is a cancer-related protein that has been implicated in the regulation of cell cycle and apoptosis. RBBP6 isoform 1 has been demonstrated to interact with two tumour suppressors, p53 and pRB. Isoform 1 been shown to regulate p53 through its ubiquitin ligase activity, thus implicating in cell cycle regulation and apoptosis. Isoforms 1 and 2 are multidomain proteins containing a domain with no name (DWNN) domain, a Zinc Finger, a RING Finger, an Rb-binding domain and a p53-binding domain. The RBBP6 isoform 3 comprises the DWNN domain only. Isoform 4 lacks the Rb-binding domain but its role is less understood. RBBP6 isoform 3 has been reported as a cell cycle regulator with anticancer potential. There have been several studies that have clearly demonstrated that RBBP6 may be an important biomarker for cancer diagnosis and a potential drug target for cancer treatment. This work focused on differential expression of RBBP6 transcripts in different cancers, providing detailed analysis of their potential as diagnostic biomarkers for different cancers. These cancers include breast, liver, cervical and colon carcinomas. The expression of RBBP6 transcripts may further provide better understanding of the role of the RBBP6 in carcinogenesis and cell homeostasis.